ISTILAH, TUGAS, DAN PENDIDIKAN HAM DALAM PERSPEKTIF KONSTITUSIONAL: ANALISIS KASUS PELANGGARAN HAK ATAS PENDIDIKAN DI INDONESIA - Maria Susanti; Nesi Rosalinda Kenjam; Maria Delastrada Namang; Heronsius Sani Ritan; Fadil Mas'ud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACTThis study discusses the right to education as part of Human Rights (HAM) from a constitutional perspective in Indonesia, and analyzes the ongoing violations of this fundamental right. Although the right to education is guaranteed in Article 31 of the 1945 Constitution and its derivative regulations, the reality reveals persistent inequality in access, discrimination, and weak implementation by state institutions. This research employs a normative-juridical method with constitutional and case-study approaches. The findings indicate that the fulfillment of the right to education remains ineffective due to unequal distribution of resources, lack of supervision, and weak integration of human rights education in the national curriculum. Human rights education needs to be strengthened as a preventive strategy to raise awareness of educational rights. Synergy between the government, human rights institutions, and civil society is essential to ensure that education is truly realized as a constitutional right.Keywords: Human Rights, Education, Constitution